DAMPAK DIVERSIFIKASI PRODUK BERBASIS AUGMENTED REALITY TERHADAP PENINGKATAN PENJUALAN DAN PERTUMBUHAN LABA UMKM GEDEBOG.IDN SURABAYA - Sandy, Wulan Mel; Susilowibowo, Joni (STKIP Persada Khatulistiwa Sintang, 2024)
Business growth is characterized by an increasing number of sales However, this condition seems difficult for MSMEs because they have not been able to withstand competition, maintain customer satisfaction, and attract buying interest. Therefore, to increase sales, it is necessary to diversify products to attract customers to buy. The existence of this tirk power is expected to create an increase in sales. The purpose of this research is used to determine the impact of product diversification using augmented reality technology on increasing sales and profit growth during the September-November period in 2023 at UMKM gedebog.idn Surabaya. The research method used is quantitative descriptive research method Data obtained from primary data The study population consisted of all sales volume and profit data during June-November 2023. Sampling data using purposive sampling using samples of sales volume and profits in September-October 2023. The results showed that product diversification using augmented reality has positive results on increasing sales in the range of 26-41% and profit growth in the range of 24-28%.